Mental and general health at the edges of owner occupation - Truong, Nguyen Tuan Khuong; Smith, Susan; Wood, Gavin; Clark, William; William, Lisowski; ViforJ, Rachel (Emerald, 2023)
Purpose The purpose of this paper is to consider one test of a well-functioning housing system – its impact on wellbeing. Exploring one indicator of this, this study aims to track changes in mental and general health across a mix of tenure transitions and financial transactions in three jurisdictions: Australia, the UK and the USA.